Insights Into Non-coding RNAs as Novel Antimicrobial Drugs - Parmeciano Di Noto, Gisela; Molina, María Carolina; Quiroga, Cecilia (Frontiers in Genetics, 2019)
Multidrug resistant bacteria are a serious worldwide problem, especially carbapenem-resistant Enterobacteriaceae (such as Klebsiella pneumoniae and Escherichia coli), Acinetobacter baumannii and Pseudomonas aeruginosa. Since the emergence of extensive and pan-drug resistant bacteria there are few antibiotics left to treat patients, thus novel RNA-based strategies are being considered. Here, we examine the current situation of different non-coding RNAs found in bacteria as well as their function and potential application as antimicrobial agents. Furthermore, we discuss the factors that may contribute in the efficient development of RNA-based drugs, the limitations for their implementation and the use of nanocarriers for delivery.